2023
DOI: 10.1021/acsami.3c00664
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Light and X-ray Charging in Persistent Luminescence Nanoparticle Scintillators Zn2SiO4:Mn2+, Yb3+, Li+

Abstract: Persistent luminescence nanoparticle scintillators (PLNS) have been attempted for X-ray-induced photodynamic therapy (X-PDT) because persistent luminescence after ceasing radiation can make PLNS use less cumulative irradiation time and dose to generate the same amount of reactive oxygen species (ROS) compared with conventional scintillators to combat cancer cells. However, excessive surface defects in PLNS reduce the luminescence efficiency and quench the persistent luminescence, which is fatal to the efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Recently, Han et al reported that Li + and Yb 3+ co-doping in Zn 2 SIO 4 :Mn 2+ ,Yb 3+ could enhance luminescence by shifting the crystal to the favourable phase. 210 A coexistence of α phase (410) and β phases (023) is present in Zn 2 SiO 4 , where the nanocrystals exhibit the most optimal afterglow time and luminescence intensity with an α / β ratio of 2.76 (Fig. 19c).…”
Section: X-ray-excited Luminescencementioning
confidence: 97%
See 1 more Smart Citation
“…Recently, Han et al reported that Li + and Yb 3+ co-doping in Zn 2 SIO 4 :Mn 2+ ,Yb 3+ could enhance luminescence by shifting the crystal to the favourable phase. 210 A coexistence of α phase (410) and β phases (023) is present in Zn 2 SiO 4 , where the nanocrystals exhibit the most optimal afterglow time and luminescence intensity with an α / β ratio of 2.76 (Fig. 19c).…”
Section: X-ray-excited Luminescencementioning
confidence: 97%
“…209 To improve the X-ray excited afterglow of the nanosystem, other Zn-based nanosystems were developed, namely, zinc gallate (ZnGa 2 O 4 ), zinc silicate (ZnSi 2 O 4 ), or variations of zinc gallogermanate. 210 X-ray-activated ZnGa 2 O 4 :Cr 3+ was first discovered in 2017 by Hao's group. 211 They reported ZnGa 2 O 4 :Cr 3+ , which exhibited 6 hours of persistent luminescence at 700 nm after the cessation of the soft X-ray excitation source with low excitation power (45 kVp, 0.5 mA), due to the characteristic electron transition of Cr 3+ from 2 E to 4 A 2 (Fig.…”
Section: X-ray-excited Luminescencementioning
confidence: 99%
“…Similarly, RB was also introduced to couple with SiO 2 @Zn 2 SiO 4 :Mn 2+ , Yb 3+ , Li + for effective persistent energy transfer and HeLa cancer cell killing by Han's group. 1252 Considering that the body needs NPs that can break down into non-toxic or low-toxic ions and be eliminated quickly without posing a long-term toxicity risk, Chen et al described a nanosystem with a silica layer loaded with merocyanine 540 (MC 540) and SrAl 2 O 4 :Eu 2+ (SAO). 1253 SAO with XEOL feature could induce MC 540 to produce ROS for X-PDT.…”
Section: Biomedical Applications Of Silicon-containing Biomaterialsmentioning
confidence: 99%
“…Additional results show that the intensity of X‐ray‐induced NaYF 4 : 3 %Er PersL in the hexagonal phase was more than ten times that in the cubic phase. Very recently, Jiang et al [161] . reported a Zn 2 SiO 4 : Mn 2+ , Yb 3+ , Li + PersL nanoscintillators with coexistence of α‐ and β‐phases.…”
Section: Tuning Of Persl Propertiesmentioning
confidence: 99%